Moderasi Beragama Menurut Islam dan Kristen - Pulungan, Mukhairimul Azmi (ANWARUL, 2023)
In the view of Islam and Christianity, religious moderation always creates differences. Differences in any field always lead to conflict. If it is not resolved properly, it will have the potential to create extreme attitudes that always justify limited choices, exacerbate religious life, and hinder the unity and integrity of the existing nation, society and state. Therefore, a solution is urgently needed that can provide peace and happiness in religious life, this is where the role of religious moderation is needed which is believed to be able to respect the diversity of choices and save us from extremism, intolerance and acts of violence. This study aims to find out how the concept of religious moderation in Islam and Christianity is compared and to increase the knowledge of students of the Study of Religions about the concept of religious moderation in the religious field according to Islam and Christianity. The research method used by researchers is the theological approach method. While the theoretical approach is comparative theory. Comparative theory or comparison is educational research that uses techniques to compare an object with another object. The data used in this research is Library Research. The primary data source is the main data source that the researcher collects directly from the research object. As for primary and secondary sources. The results of this study are; moderation in the form of Aqidah in Islam Moderation in the field of creed, moderation in Religious Thoughts: Between Textual and Liberal in Islam and Christianity, moderation in Interreligious Interaction in Islam, namely by the existence of Wasathiyah teachings in Islam and Christianity.